2017
DOI: 10.1086/690109
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the use of oral treprostinil in clinical practice: a Delphi consensus project pulmonary circulation

Abstract: Oral treprostinil was recently labeled for treatment of pulmonary arterial hypertension. Similar to the period immediately after parenteral treprostinil was approved, there is a significant knowledge gap for practicing physicians who might prescribe oral treprostinil. Despite its oral route of delivery, use of the drug is challenging because of the requirement for careful titration and management of drug-related adverse effects. We aimed to create a consensus document combining available evidence with expert o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Baughman) have extensive experience organising initial panels of experts and have previous experience conducting Delphi studies that have resulted in publications that are used by physicians in clinical practice. The prior studies produced consensus recommendations for the use of oral treprostinil for pulmonary arterial hypertension [22] and recommendations on the clinical management of pulmonary arterial hypertension patients receiving macitentan [23], in addition to the recommendations on a treatment algorithm for sarcoidosis in this series [13].…”
Section: Discussionmentioning
confidence: 99%
“…Baughman) have extensive experience organising initial panels of experts and have previous experience conducting Delphi studies that have resulted in publications that are used by physicians in clinical practice. The prior studies produced consensus recommendations for the use of oral treprostinil for pulmonary arterial hypertension [22] and recommendations on the clinical management of pulmonary arterial hypertension patients receiving macitentan [23], in addition to the recommendations on a treatment algorithm for sarcoidosis in this series [13].…”
Section: Discussionmentioning
confidence: 99%
“…32,33 A recent Delphi panel on the use of oral treprostinil suggested aggressive antidiarrheal medication to manage these adverse effects, but failed to reach consensus on optimal dosing strategies. 34 In FREEDOM-EV, oral treprostinil was dosed TID; 21 although this could help reduce the intensity of adverse effects to allow increasing the dose to a therapeutic level, 34 TID dosing could introduce adherence issues compared with a drug with less frequent dosing. 35,36 The primary limitation of this study is that whereas the index drugs are indicated solely for specified patients with PAH (not other forms of PH) there is no unique ICD-9-CM or ICD-10-CM code for PAH.…”
Section: Clinical Guidelines Current During the Study Period Gave A Cmentioning
confidence: 99%
“…Attrition due to AE typical for prostacyclin class medication was ~13% in the initial short-term studies and continued during the open-label extension, but AE may be less intense with a TID dosing strategy. 21…”
Section: Limitationsmentioning
confidence: 99%